2009
DOI: 10.4321/s1886-36552009000400008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of educational intervention on the pattern and incidence of potential drug-drug interactions in Nepal

Abstract: *Objective: To study the impact of educational intervention on the pattern and incidence of potential drug-drug interactions (DDIs). Method: All patients admitted to Internal Medicine wards of Manipal Teaching Hospital during the study period were included. Patient details were collected using a patient profile form and the datum from the filled forms was analyzed using Micromedex electronic database. An intervention was carried out through a presentation during clinical meeting and personal discussion. The ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 20 publications
4
18
1
Order By: Relevance
“…[1][2][3][5][6][7][8][9][12][13][14][15][16][17][18] The present study also shows a statistical association between polypharmacy and number of pDDI.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…[1][2][3][5][6][7][8][9][12][13][14][15][16][17][18] The present study also shows a statistical association between polypharmacy and number of pDDI.…”
Section: Discussionsupporting
confidence: 57%
“…[5][6][7]9,12,[15][16][17] Hence, we can say that pDDI are more common in elderly probably due to age related physiological, pharmacokinetic and pharmacodynamic changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are few studies that can be directly compared with this study because these studies have also used Micromedex database to check the severity of interaction. These few studies had shown DIs in the range of 1.5-28% of severe drug interactions in hospitalized elderly patients 8,9,10,11. Only one study has reported a very low rate (1.5%) 8.…”
Section: Discussionmentioning
confidence: 99%